2022
DOI: 10.1111/ans.17921
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term outcomes following development of a dedicated pelvic exenteration service in a tertiary centre

Abstract: Background: Pelvic exenteration surgery (PE) offers potentially curative resection for locally advanced malignancy but is associated with significant complexity and morbidity. Specialised teams are recommended to achieve optimal patient outcomes. This study aims to analyse short-term outcomes at a tertiary setting before and after creating a dedicated PE service. Methods: Patients undergoing PE between 2008 and October 2021 at the Royal Adelaide Hospital and St. Andrews Hospital in South Australia were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Recognizing that the current data are collected from a 12-month period, the number of referrals to interstate centres has reduced from all three LHN's collectively. 1,17 This may reflect the presence of a surgeon from RPAH at the MDT but is also likely the result of progress and development in specialist expertise available within SA. A recent publication from the RAH exenteration unit has demonstrated that more complex operations are being performed on patients with more advanced disease and increased comorbidities without compromising patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recognizing that the current data are collected from a 12-month period, the number of referrals to interstate centres has reduced from all three LHN's collectively. 1,17 This may reflect the presence of a surgeon from RPAH at the MDT but is also likely the result of progress and development in specialist expertise available within SA. A recent publication from the RAH exenteration unit has demonstrated that more complex operations are being performed on patients with more advanced disease and increased comorbidities without compromising patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication from the RAH exenteration unit has demonstrated that more complex operations are being performed on patients with more advanced disease and increased comorbidities without compromising patient outcomes. 17 While it is anticipated that interstate referrals may naturally decline over time with increased local experience, the need for better coordination is already recognized. Seizing the opportunity for better processes now has been a key element in addressing the increased demand for pelvic exenteration services in SA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who underwent PE for colorectal cancer, gynaecological malignancy, sarcoma, or benign disease between May 2008 and November 2022 at the Royal Adelaide Hospital and St. Andrews Private Hospital in South Australia were retrospectively identified from a prospectively maintained database set up for the PelvEx collaborative as previously reported [ 17 ]. All patients were scheduled for PE based on computed tomography (CT), positron emission tomography (PET), or magnetic resonance imaging (MRI), and multi-disciplinary team (MDT) discussion.…”
Section: Methodsmentioning
confidence: 99%